Visual rhetoric of the Presidency: an analysis of the Trump and Obama White House messaging in their first 100 days in Flickr images. Issue 1 (2nd January 2018) - Chun, Russell Scott
Abstract: In this study, we examine images released by the White House on Flickr, an online public photo sharing site, to identify the visual messaging of the Trump Presidency in their first 100 days and compare it to the previous Obama administration. We draw on Burke's dramatistic pentad and agenda setting theories to tag images in a qualitative data analysis. Our results indicate that the Trump administration frames a visual narrative, consistent with its campaign rhetoric that celebrates power with allusions to authoritarian tropes, emphasizes the singularity of the President, and glorifies his claim of widespread popularity. Our examination also corroborates an aesthetic mediocrity, which we interpret as an anti-design disposition embraced by Trump's supporters who may disparage design as an elitist endeavor even if it contradicts Trump's reputation as the consummate showman. Our findings offer a valuable adjunct to traditional analyses of political communication.